Spiritual and Physical Aspect in Cultural Sport “Pencak Silat Harimau Putih” Based on Pesantren Literature - Muhammad Abdullah; Amirudin Amirudin (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Pesantren (Islamic Boarding School) Literature is a collection of literary works of books (religious literature), oral literary works, and written literature created and developed in the environment of Pesantren. Pesantren literature is in the form of oral and written traditions containing moral, fiqh, tauhid, tasawuf, theology, and syi'ir works, nasyid and others. Among the literary works of pesantren containing esoteric aspects of Islam, as written by Abdullah in the Khazanah Sastra While the oral literary works that still exist in the tradition of pesantren is wirid, hizb, pilgrimage, istighotsah, blantenan, Pencak Silat Asmaul Husna, Pencak Silat Harimau Putih (Indonesian Martial Arts), and others.  Oral Traditions are sometimes read and performed in religious rituals, such as birth ceremonies, circumcisions, and other celebrations. The aims of the paper are to investigate the combination of spiritual and physical aspect in traditional sport using literature methode and field survey.  The oral tradition of Pencak Silat Harimau Putih in Kaliwungu Kendal is a hereditary heritage from Prabu Siliwangi. As a vehicle of tarekat tradition, this martial art can be used as a means of communication between man and his God, and among fellow human beings. In practice, Pencak Silat Harimau Putih accompanied by footsteps and hand movements. This in addition to functioning as a sport and entertainment, also serves as a means of worship and endeavor to defend themselves in society to survive and maintain, preserve the existence to face the challenges of the times.